STRATEGI MANAJEMEN RISIKO DALAM EKOSISTEM FINTECH: PENDEKATAN SYSTEMATIC LITERATURE REVIEW (SLR) - Eka Suryana; Muhammad Zilal Hamzah; Eko Retno Indriyarti (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2025)
This study aims to systematically analyze risk management strategies within the fintech ecosystem by emphasizing the dimensions of technology, governance, and regulation. This study employed a Systematic Literature Review (SLR) approach, adhering to the PRISMA 2020 framework, to ensure a transparent and systematic literature selection process. In the identification stage, researchers collected 645 articles from Google Scholar, Scopus, and DOAJ databases spanning 2015–2025 using keywords related to risk management and fintech. Subsequently, a screening stage was conducted by filtering out duplications and selecting relevant titles and abstracts, significantly reducing the number of articles. In the eligibility stage, the remaining articles were fully reviewed based on inclusion criteria such as topic relevance, publication quality, and adequate data availability. In the inclusion stage, 24 articles were selected for further analysis using a thematic approach to identify patterns of risk management strategies in the fintech ecosystem. The findings indicate that fintech risks are classified into three main dimensions, namely technological, institutional, and regulatory risks. The most adaptive mitigation strategies are associated with the application of ISO 31000 and COSO Enterprise Risk Management (ERM), emphasizing the integration of risk supervision, organizational governance, and digital technology. Furthermore, effective fintech risk management is strongly influenced by collaboration among regulators, industry players, and the public in creating transparent, responsive, and inclusive supervisory systems. Compared to previous studies, this research offers a more comprehensive synthesis by integrating risk governance frameworks with emerging digital approaches such as RegTech and SupTech, and highlights the importance of combining technological innovation, internal governance, and cross-sector collaboration into a unified risk management model within the fintech ecosystem.